유산소 걷기 운동이 중년여성의 복부피하지방조직의 싸이토카인 유전자 발현에 미치는 영향 - 강현식; 안의수 (Exercise science (Seoul, Korea), 2011)
본 연구의 목적은 중년여성을 대상으로 정상집단(n=12), 비만집단(n=10), 대사증후군+비만(n=10)집단으로 세분화하여 다음 5개월 걷기 운동을 적용함으로서 유산소 운동이 인슐린저항성지표, 혈청 싸이토카인, 복부피하지방조직의 싸이토카인 유전자 발현에 미치는 영향을 비교하는 것으로 하였다. 걷기 운동 강도는 최대산소섭취량의 65%, 빈도는 주당 3회, 기간은 5개월로 설정했으며, 걷기 운동 프로그램 사전 및 사후 공복상태에서 신체구성(신장, 체중, 체지방), 심폐체력, 혈당, 인슐린, 호마지수, 싸이토카인, 복부피하 및 내장지방, 복부피하지방의 싸이토카인 유전자발현 등을 측정 및 분석하였다. 측정한 종속변인에 대해 이원혼합변량분석을 적용하여 측정시기 및 집단 간 차이를 비교한 결과, 첫째 걷기 운동은 모든 집단의 비만지표, 인슐린저항성, 혈청 인슐린저항성 싸이토카인, 복부피하지방조직의 인슐린저항성 싸이토카인 유전자 발현을 개선시키는데 효과적인 것으로 나타났다. 둘째, 호마지수, 렙틴 혈청 수준, 복부피하 지방조직의 렙틴 유전자 발현의 경우 측정시기와 집단 간에 유의한 상호작용효과가 있는 것으로 나타났다. 유의한 상호작용 효과에 대해 사후검정을 실시한 결과, 호마지수, 혈청 렙틴, 복부피하지방조직의 렙틴 유전자 발현에 대한 걷기 운동의 긍정적인 효과는 정상체중과 비만집단에 비해 대사증후군+비만집단에서 통계적으로 유의하게 더 높은 것으로 확인되었다. 전체집단을 대상으로 다중선회귀분석을 적용한 결과 혈중 렙틴 수준의 감소 정도는 5개월 걷기 운동에 의한 호마지수의 개선을 예측하는데 가장 중요한 독립예측변인인 것으로 밝혀졌다. The purpose of the present study was to investigate the effects of a 5-month walking program on abdominal body fatness, insulin resistance markers, serum cytokines, and cytokine genes in abdominal subcutaneous adipose tissues(SAT) in middle-aged women. Normal(n=12), obesity(n=10), and obesity+metabolic syndrome(MS) (n=10) groups participated in a walking exercise program(intensity=65% VO2max, frequency=3 days/week, duration=5 months). Percent body fat, CT-based abdominal visceral(VAT) and subcutaneous adipose tissue(SAT), fasting glucose, insulin, serum and SAT mRNA levels of cytokines(i.e., adiponectin, leptin, vaspin, IL-6, TNF-α, resistin) were measured prior to and after the walking program. Two-way ANOVA analyses with mixed design showed significant time×group interaction effects for homeostasis assessment model for insulin resistance(HOMA-IR), serum leptin, and SAT leptin mRNA expression. Following the walking program, the obesity+MS group had highest improvements in HOMA-IR, serum leptin, and SAT leptin mRNA levels followed by those of the obesity group and the normal group, respectively. In addition, participating in a 5-month walking program improved body fatness, insulin resistance markers, serum cytokines, and SAT mRNA expression in all the groups. Multivariate linear regression analysis showed that changed serum leptin was the only significant predictor for individual variations in changed HOMA-IR following a 5-month walking program in this study sample. KCI Citation Count: 18